The Role of the Samapta Patrol Unit in Preventing Theft by Force at Polresta Magelang - Kalyana, Arkan (Advances in Police Science Research Journal, 2024)
Theft with violence is a crime that often occurs in Indonesia. These crimes are generally caused by socio-economic factors that often occur in areas with high inequality, one of which is Magelang Regency. This study aims to describe the roles and factors that influence the performance of the SatSamapta patrol unit in improving the prevention of criminal acts of fraud in the jurisdiction of the MageIang Police Station using management theory and organizational resources. The concepts used are the concepts of samapta units, patrols, and theft by force. Discussion and problems in this study to be carried out effectively, so in this study using qualitative methods with a field study approach. The location of this research is in the legal area of Poliresta MageIang. The results of this study indicate that the implementation of patrols by the Satsamapta Polesta Police Magelang Patrol Unit is still not fully in accordance with Perkabaharkam No. 1 of 2017. Implementation management starting from planning, organizing, implementing and controlling is not yet optimal. Planning activities that are carried out sometimes do not follow the intelligence assessment and the results of Anev Disruption of Kamtibmas. In addition, the lack of members of the Patrol Unit makes the implementation of Patrols less than optimal to improve the prevention of criminal acts of fraud. In its implementation, the AAP that was carried out did not lead to the implementation and division of tasks that were carried out. The Satsamapta Police MageIang Turjagwali Unit has carried out various preventive efforts in maintaining security and order, especially criminal acts of cheating through dialogic patrols, especially to local security officers such as housing security guards, banks, and places that have the potential for security and order disturbances. Good communication and cooperation with the community is very helpful in implementing the patrol unit in maintaining law and order in the legal area of the Magelang Police Headquarters.